2002
DOI: 10.1034/j.1600-0625.2002.110303.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in cytokine regulation in aged epidermis: implications for permeability barrier homeostasis and inflammation

Abstract: Acute disruption of the cutaneous permeability barrier with either solvents or tape-stripping stimulates a homeostatic metabolic response in the subjacent nucleated layers of the epidermis that results in a rapid restoration of normal permeability barrier function. When the aged epidermal permeability barrier is stressed, it reveals a diminished capacity for recovery, in comparison to young epidermis, analogous to other organs in the aged when stressed. Although the signals that regulate this homeostatic respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 38 publications
2
47
0
Order By: Relevance
“…Interestingly, the omega-3 polyunsaturated fatty acid 11,14,17-eicosatrienoic acid was found to be increased in photoaged human epidermis and also after UV irradiation, whereas a decrease was found in intrinsically aged human epidermis [33]. A deficiency of IL-1 signaling in murine aged epidermis, which may contribute to epidermal barrier abnormality, has been reported by Ye et al [23]. An improvement in barrier recovery has been achieved with the administration of imiquimod to aged murine skin, as imiquimod induces an alteration in multiple cytokine pathways, including an increase in IL-1α levels, and this seems to improve barrier recovery in aged epidermis [23,34].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Interestingly, the omega-3 polyunsaturated fatty acid 11,14,17-eicosatrienoic acid was found to be increased in photoaged human epidermis and also after UV irradiation, whereas a decrease was found in intrinsically aged human epidermis [33]. A deficiency of IL-1 signaling in murine aged epidermis, which may contribute to epidermal barrier abnormality, has been reported by Ye et al [23]. An improvement in barrier recovery has been achieved with the administration of imiquimod to aged murine skin, as imiquimod induces an alteration in multiple cytokine pathways, including an increase in IL-1α levels, and this seems to improve barrier recovery in aged epidermis [23,34].…”
Section: Discussionmentioning
confidence: 89%
“…Choi et al showed that the increased vulnerability of aged skin is due to abnormal SC acidity, resulting in defective lipid processing and loss of SC integrity [16]. Table 1 summarizes known changes in epidermal barrier function during aging [9,16,17,18,19,20,21,22,23,24], which may affect pH SC and pH SS .…”
Section: Introductionmentioning
confidence: 99%
“…The number or function of T cells and B cells deteriorate (Effros, 2001;Gardner and Murasko, 2002;Grubeck-Loebenstein and Wick, 2002) while the effects of age on innate immune cells, such as macrophages have been widely investigated (Plackett et al, 2004). In human skin, cytokine dysregulation, particularly of the interleukin (IL)-1 family has been described to contribute to ageing (Ye et al, 2002) and disturbed skin barrier function. The microinflammatory model of skin ageing postulates that every stimulus able to induce the synthesis of intercellular adhesion molecule-1 (ICAM-1) in the endothelium is a factor of skin ageing.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Although cholesterol synthesis rates are high under basal conditions, following permeability barrier disruption, epidermal cholesterol synthesis increases ( 3 ), as do the levels of receptors such as the LDL receptor and scavenger receptor class B, member 1 that enhance the uptake of cholesterol into keratinocytes ( 4, 5 ). Inhibition of cholesterol synthesis perturbs permeability barrier function ( 6 ), and a selective deficiency in cholesterologenesis largely accounts for the barrier abnormality in chronologically aged epidermis ( 7,8 ). Cholesterol is also the precursor of an important bioregulatory molecule in keratinocytes, cholesterol sulfate (CS), which regulates epidermal keratinocyte differentiation ( 9-11 ) and corneocyte desquamation by diverse mechanisms ( 12, 13 ).…”
Section: Journal Of Lipid Researchmentioning
confidence: 99%